2020
DOI: 10.1016/j.marpetgeo.2020.104646
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation on methane hydrate morphologies and pore habits in sandy sediment using synchrotron X-ray computed tomography

Abstract: As pore-scale morphologies and spatial distribution (pore habits) of natural gas hydrates in marine sediments considerably affect their physical/mechanical properties, they have extensively been investigated by X-ray computed tomography (XRCT) and especially synchrotron X-Ray computed tomography (SXRCT). While both image spatial and scan temporal resolutions are being improved over time, it is still challenging to distinguish water from methane hydrate in an image due to their low absorption contrast. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 42 publications
(63 reference statements)
2
27
0
Order By: Relevance
“…(2016) . This is because although water can migrate among the sand particles ( Le et al., 2020 ; Nikitin et al., 2020 ), it is still physically impossible to float at the pore space in a gas excess environment. Figure 1 E shows the hydrate spatial distribution influence on the radii distribution of the pore space.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2016) . This is because although water can migrate among the sand particles ( Le et al., 2020 ; Nikitin et al., 2020 ), it is still physically impossible to float at the pore space in a gas excess environment. Figure 1 E shows the hydrate spatial distribution influence on the radii distribution of the pore space.…”
Section: Resultsmentioning
confidence: 99%
“…Xenon gas is used to generate xenon hydrate (XeH) instead of methane gas to enhance the phase contrast in the CT images. Moreover, it must be noted that the physical characteristics between the XeH and NGH are also quite close ( Chaouachi et al., 2015 ; Ning et al., 2012 ), as are the pore-scale occurrences between XeH and NGH following the similar formation procedure ( Lei et al., 2019 ; Le et al., 2020 ). Furthermore, the substitutability of XeH for NGH for some pore-habit evolution studies has been widely accepted ( Chaouachi et al., 2015 ; Yang et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed growth mechanism would lead to hydrate growth stiffening up particle contacts from the outset, which is supported by the rapid increase in G max as hydrate formation proceeds (Figure 4) as observed in our tests as well as others (Clayton et al, 2005;Sultaniya et al, 2018) where the excess-gas method is used. using X-ray CT imaging suggest that in a gas-saturated environment hydrate growth occurs on the mineral surfaces and grows into the pore space, while Le et al (2020) showed that both mineral coating hydrate and hydrate at grain contacts can exist locally. Given the small sampling size used in CT studies, it is highly probable that at the specimen scale extensive grain contacts "cemented" by hydrate exists that leads to the large stiffening effect.…”
Section: Factors Affecting G Max During Hydrate Formationmentioning
confidence: 99%
“…Even though it is helpful to build geophysical and reservoir models, this categorization of hydrate distribution within the pore space lacks direct experimental confirmation. The very scarce high-resolution imaging studies by means of synchrotron X-ray computed tomography (XRCT) in fact point to more complex features of gas hydrate formation and growth in sediment pores [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%